(untitled) (World Economics and Finance Bulletin, 2022)
Increasing the level of financial literacy of the population is a necessary part of the rapid development of any country involved in international economic relations, including modern Uzbekistan. In such a situation, one of the main goals set by the government is to "arm" citizens with information and educational tools for effective management of personal funds and, as a result, equal participation in the socio-economic life of the country. Solving this problem requires an integrated approach and the involvement of experts from various structures and organizations of regional organizations in this process. This article focuses on the role of state and commercial banks in improving the financial literacy of the population, their role and importance in providing the economic knowledge of the population today.